So You Want to Know About The Environment - Bijal Vachharajani (New Delhi, India Rupa Publications, 2017)
Ever wondered what it is like to live on a planet that$1 (Bs a few degrees warmer, or how wasting food is the similar to flushing water down the drain, or what exactly does the word planned obsolescence mean. So You Want to Know About the Environment answers some of the questions about the world we live in, and how we impact it in different ways.s
Keywords: Narrative Nonfiction -- Narrative Nonfiction